Methodology of Solving Complex Problems of Permanent Electric Chains - Zaynidinovna, Muattar Jiyanboeva; Orinbaevna, Zamira Khamraeva (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents the optimal methods for solving typical problems of the "DC" section, as well as some methods for calculating complex electrical circuits, which can be used to solve problems related to electrical circuits. This will enhance the pace of problem solving of university entrants.